2007
DOI: 10.1111/j.1365-2125.2007.02925.x
|View full text |Cite
|
Sign up to set email alerts
|

Foundation year 1 doctors and clinical pharmacology and therapeutics teaching. A retrospective view in light of experience

Abstract: What is already known about this subject • In the UK prescribing-related errors are common.• Poor prescribing and prescribing errors result in significant patient morbidity and mortality.• In hospital, junior doctors are responsible for a significant number of prescribing errors. AimsTo determine whether, in retrospect, first year foundation (FY1) programme doctors believe that their undergraduate education in Clinical Pharmacology and Therapeutics (CPT) has prepared them to prescribe safely and rationally. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 8 publications
10
118
0
1
Order By: Relevance
“…While students should not be expected to remember exact drug doses, except perhaps for a small number of emergency drugs, they should know where to find information quickly and easily and understand the principles that underlie rational dose selection. This is an aspect that students and new doctors are often particularly concerned about and seek further guidance [3]. Students should also have a clear understanding of their responsibilities as prescribers and the limits of their competence.…”
Section: Essential Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…While students should not be expected to remember exact drug doses, except perhaps for a small number of emergency drugs, they should know where to find information quickly and easily and understand the principles that underlie rational dose selection. This is an aspect that students and new doctors are often particularly concerned about and seek further guidance [3]. Students should also have a clear understanding of their responsibilities as prescribers and the limits of their competence.…”
Section: Essential Drugsmentioning
confidence: 99%
“…While there remain concerns from some that a return to allowing unqualified staff to write on official documentation constitutes an unnecessary risk we believe that this represents an illogical and short-sighted approach to risk management.The final year medical students of this month may be next month's busiest hospital prescribers, competence assumed, and often poorly supervised. Various studies have highlighted that this transition currently involves an unreasonable jump in responsibility [2,3,5,6]. Pre-prescribing offers the opportunity to bring the steepest part of the 'learning curve' into undergraduate training where there is less time pressure and better supervision for the novice prescriber.…”
Section: Prescribing Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey data of Foundation Year 1 doctors at a teaching hospital in Scotland identified that undergraduate and postgraduate training in clinical pharmacology and therapeutics was considered by them to be insufficient to promote rational and safe use of medicines [17]. In an attempt to meet some of these learning needs, the British Pharmacological Society has recently launched e-Prescribe, which aims to provide e-learning materials to help medical students (and students from other healthcare professions) develop a firm grounding in the principles of basic and clinical pharmacology and hence promote safe and effective prescribing [18].This is one of many initiatives available to develop and improve prescribing skills.…”
Section: Stronglymentioning
confidence: 99%
“…First-year doctors are neither confident nor competent when prescribing, by their own assessment and that of their supervisors [5,6]. New prescribers have also highlighted a lack of undergraduate and postgraduate education in prescribing [7,8].…”
Section: Introductionmentioning
confidence: 99%